2011
DOI: 10.1002/pon.2092
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic stress in acute leukemia

Abstract: The present study demonstrates that clinically significant symptoms of traumatic stress are common in acute leukemia and are linked to the degree of physical suffering, to satisfaction with relationships with health-care providers, and with individual psychological characteristics. Longitudinal study is needed to determine the natural history, but these findings suggest that intervention may be indicated to alleviate or prevent traumatic stress in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
85
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(91 citation statements)
references
References 51 publications
2
85
2
2
Order By: Relevance
“…The diagnosis of AML results in significant psychological distress [31] and treatment with IC is associated with serious physical and psychological complications that can potentially impact QOL [32,33]. However, potential age-related differences in perceived physical and psychosocial challenges of living with leukemia and its treatment, as well as adopted coping strategies and expected health care support, have not been reported previously to our knowledge.…”
Section: Discussionmentioning
confidence: 79%
“…The diagnosis of AML results in significant psychological distress [31] and treatment with IC is associated with serious physical and psychological complications that can potentially impact QOL [32,33]. However, potential age-related differences in perceived physical and psychosocial challenges of living with leukemia and its treatment, as well as adopted coping strategies and expected health care support, have not been reported previously to our knowledge.…”
Section: Discussionmentioning
confidence: 79%
“…Receiving a diagnosis of AML and undergoing chemotherapy are traumatic experiences burdened with enormous physical and psychological distress [4,5,7]. Effective coping strategies are required to adjust to life with AML [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our analysis revealed that participants were affected with an overwhelming sense of loss, fear, and uncertainty in the early phase of IC [7]. Likewise, two recent cross-sectional studies on newly diagnosed AML patients receiving IC and one longitudinal study of AML patients undergoing prolonged chemotherapy documented a high prevalence of traumatic stress symptoms, intense worrying and sadness, uncertainty about durable remission, and fear of cancer recurrence as serious threat to psychological well-being [4,5,8]. Correspondingly, several qualitative studies investigating patients' perspectives on the initial phase of leukemia diagnosis, IC, and bone marrow transplantation (BMT) noted a sense of shock, emotional numbness, threat, insecurity, uncertainty, and fear regarding diagnosis, invasive procedures, cancer recurrence, and transplant rejection [9][10][11][12].…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…4 The rapid onset and fluctuating course of hematological malignancies, with frequent life-threatening complications, suggest that anxiety symptoms including posttraumatic stress disorder may be a common accompaniment. 5 Furthermore, terminal hematological cancer patients may suffer from other problems identical to those of the general cancer population, including loss of autonomy and disability. 6 From current evidence, the historical prioritization of cancer care at the center of palliative medicine did not guarantee that those diagnosed with a hematological malignancy were assured of referral, timely or otherwise.…”
Section: Optimizing End-of-life Care For Patients With Hematological mentioning
confidence: 99%